Assessment of heavy metals in soil mining areas of gwanaalkaleri lga bauchi state - Siman, Mikin; Abdulahi Shibdawa, Muhammed; Abdulahi Shibdawa, Muhammed; Malgwi Adamu, Harami; Malgwi Adamu, Harami; Lakusha, Zakaria; Lakusha, Zakaria; Collins Wuyep, Lungfa; Collins Wuyep, Lungfa; Gudam Talkat, Maxwell; Gudam Talkat, Maxwell; Nashuka Kaigama, Williams; et al. (International Journal of Advanced Chemistry, 2021)
Analysis of soil were carried out on mining areas and adjourning farmlands around Gwana in Alkaleri Local Government Area of Bauchi State. The physico–chemical analysis conducted includes pH, electrical conductivity and moisture content which was accompanied by the geochemical characterization and quantification of the metal ions present in the soil. The pH of the soil was within the ranges from 5.6 ±0.01–6.7±0.01, electrical conductivity was within the ranges of 185–290mS/cm and percentage moisture content was within the ranges from 0.42–3.30. the geochemical characterization revealed the presences of chromium (11±0.02 mg/Kg), cobalt (0.1–2.1 mg/Kg), copper (21.9 ±0.01–92.5 ±0.01 mg/Kg), iron (48 ±0.01–174 ±0.01 mg/Kg), lead (7.9 ±0.01–215 ±0.01 mg/Kg), manganese (19.8– 164.8 mg/Kg), nickel (2.9 ±0.01–3.4 ±0.01 mg/Kg), silver (0.4 ±0.01–2.1±0.01 mg/Kg) and zinc (299 ±0.01–417 ±0.01mg/Kg). The concentration of metal ions of copper, lead and zinc in the soil samples collected from the study area revealed that they were excessively above their permissible limit set by the WHO, both in the areas of active mining operations and in the adjourning farmland. Hence the conclusion that the soils where contaminated as a result of the mining activities being carried out within the locality. Based on the high levels of these metal ions in the soils analyzed from the study area, it is hereby recommended that crop samples from within the catchment areas understudy should also be analyzed to evaluate their bioaccumulation coefficient, mobility index and their potential health risk index if any, that may arise from their being exposed to mining activity within the area.